2021
DOI: 10.1111/bcp.14855
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glucagon‐like peptide‐1 receptor agonists on adiponectin concentrations: A meta‐analysis of randomized controlled trials

Abstract: Previous studies have reported an elevation in adiponectin concentrations using glucagon-like peptide-1 receptor agonists (GLP-1 RA) therapy; however, this possible pleiotropic effect is still uncertain. Thus, the objective of this meta-analysis of randomized controlled trials was to assess the impact of GLP-1 RA on adiponectin levels.Methods: This systematic review and meta-analysis included randomized controlled trials investigating the effect of GLP-1 RA on circulating adiponectin concentrations.Studies fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…In fact, both in vivo and in vitro studies, have reported that adiponectin deficiency would trigger an increase in osteoclastogenesis, adipogenesis and a reduction in osteogenesis [ 29 ] . This data confirms a recent meta-analysis that evaluated the effects of GLP-1RAs on adiponectin and found that GLP-1RAs were able to increase adiponectin levels [ 30 ]. Although molecular mechanisms underlying the elevation in circulating adiponectin concentrations following GLP1-RAs are yet to be elucidated, higher values of adiponectin may reduce inflammatory cytokines and oxidative stress with positive effects on bone metabolism [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, both in vivo and in vitro studies, have reported that adiponectin deficiency would trigger an increase in osteoclastogenesis, adipogenesis and a reduction in osteogenesis [ 29 ] . This data confirms a recent meta-analysis that evaluated the effects of GLP-1RAs on adiponectin and found that GLP-1RAs were able to increase adiponectin levels [ 30 ]. Although molecular mechanisms underlying the elevation in circulating adiponectin concentrations following GLP1-RAs are yet to be elucidated, higher values of adiponectin may reduce inflammatory cytokines and oxidative stress with positive effects on bone metabolism [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…This data confirms a recent meta-analysis that evaluated the effects of GLP-1RAs on adiponectin and found that GLP-1RAs were able to increase adiponectin levels [ 30 ]. Although molecular mechanisms underlying the elevation in circulating adiponectin concentrations following GLP1-RAs are yet to be elucidated, higher values of adiponectin may reduce inflammatory cytokines and oxidative stress with positive effects on bone metabolism [ 30 ]. However, the relationships between adiponectin levels and BMD values in humans are complex and requires further studies.…”
Section: Discussionsupporting
confidence: 90%
“…GLP-1 receptors are widely distributed throughout the body and have multiple biological effects: suppressing appetite, reducing neuroinflammation, regulating blood lipid metabolism and reducing fat deposition ( 31 ). GLP-1 RAs also elevate adiponectin levels and reduce leptin levels which may have a direct effect on lymphedema ( 32 , 33 ). Adiponectin is an adipocyte complement-related protein that exhibits anti-inflammatory properties and is inversely correlated with BMI ( 34 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, strict inclu-sion criteria were applied, and studies with active controls were excluded to reduce the possible source of heterogeneity. This is important because several other antidiabetic medications have also been associated with increased plasma adiponectin, such as the dipeptidyl peptidase-4 (DPP4) inhibitors [44] and glucagon-like peptide-1 receptor agonists (GLP-1 RA) [45]. Inclusion studies with DPP4 inhibitors or GLP-1 RA as controls would confound the findings of the meta-analysis and lead to heterogeneity.…”
Section: Discussionmentioning
confidence: 99%